EXPLANATION
If the first two terms of an arithmetic sequence are 7 and 4, then we know that an arithmetic sequence has a constant difference d and is defined by
![a_n=a_1+(n+1)d](https://tex.z-dn.net/?f=a_n%3Da_1%2B%28n%2B1%29d)
Check wheter the difference is constant:
Compute the differences of all the adjacent terms:
![d=a_{n+1}-a_n](https://tex.z-dn.net/?f=d%3Da_%7Bn%2B1%7D-a_n)
Replacing terms:
4-7 = -3
The difference between all of the adjacent terms is the same and equal to
d = -3
The first element of the sequence is
![a_1=7](https://tex.z-dn.net/?f=a_1%3D7)
![a_n=a_1+(n+1)d](https://tex.z-dn.net/?f=a_n%3Da_1%2B%28n%2B1%29d)
Therefore, the nth term is computed by
d= -3
![a_n=7+\text{ (n-1)}\cdot(-3)](https://tex.z-dn.net/?f=a_n%3D7%2B%5Ctext%7B%20%28n-1%29%7D%5Ccdot%28-3%29)
Refine
d= -3 ,
![a_n=-3n+10](https://tex.z-dn.net/?f=a_n%3D-3n%2B10)
Now, replacing n=7
![a_7=-3\cdot7+10\text{ = -11}](https://tex.z-dn.net/?f=a_7%3D-3%5Ccdot7%2B10%5Ctext%7B%20%3D%20-11%7D)
So, the answer is -11.
1 and 50
2 and 25
2 and 50
5 and 50
10 and 50
25 and 50
Sense there's only a y, you'd assume y is 1 or 1y.
you'd make the 1 a negative 1 to get rid of the subtraction sign.
you'd add together the 2 ys making it 2y. then add -1 + 3, which would be 2.
so, the answer would be 2y + 2.
Answer:
-1
Step-by-step explanation:
Following PEMDAS The answer equals to -1
<u>*plssss make me brainlist*</u>
$10,000 at 7% continuous compounding for 8 years
![10000 e^{0.07 (8)} = 17506.7](https://tex.z-dn.net/?f=10000%20e%5E%7B0.07%20%288%29%7D%20%3D%2017506.7)
Answer: A